Model-Based Testing of Web Applications using NModel - Ernits, Juhan; Roo, Rivo; Jacky, Jonathan; Veanes, Margus (LNCS, TESTCOM/FATES 2009, 2009)
We show how model-based on-the-fly testing can be applied in the context of web applications using the NModel toolkit. The concrete case study is a commercial web-based positioning system called WorkForce Management (WFM) which interacts with a number of other services, such as billing and positioning, through a mobile operator. We describe the application and the testing, and discuss the test results.